1993
DOI: 10.1152/jn.1993.69.2.626
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic modulation of synaptic inhibition in the guinea pig hippocampus in vitro: excitation of GABAergic interneurons and inhibition of GABA-release

Abstract: 1. The effect of cholinergic receptor activation on gamma-aminobutyric acid (GABA)-mediated inhibitory synaptic transmission was investigated in voltage-clamped CA1 pyramidal neurons (HPNs) in the guinea pig hippocampal slice preparation. 2. The cholinergic agonist carbachol (1-10 microM) induced a prominent and sustained increase in the frequency and amplitudes of spontaneous inhibitory postsynaptic currents (IPSCs) in Cl(-)-loaded HPNs. The potentiation of spontaneous IPSCs was not dependent on excitatory sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
94
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(114 citation statements)
references
References 0 publications
19
94
1
Order By: Relevance
“…A likely explanation for this finding is that presynaptic M 2 receptors mediate suppression of GABAergic (GABA A receptor mediated) inhibition of CA1 neurons in the M2 ϩ/ϩ hippocampus. This concept is supported by previous observations indicating that M 2 receptors are present on GABAcontaining nerve terminals throughout the hippocampus (Rouse et al, 1997;Hajos et al, 1998) and that activation of hippocampal muscarinic receptors inhibits GABA release from hippocampal interneurons (Ben Ari et al, 1981;Behrends and ten Bruggencate, 1993). Together, these findings are consistent with a model in which induction of STP and LTP requires the activity-dependent stimulation of presynaptic M 2 heteroceptors suppressing the GABA-mediated inhibition of CA1 pyramidal neurons.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A likely explanation for this finding is that presynaptic M 2 receptors mediate suppression of GABAergic (GABA A receptor mediated) inhibition of CA1 neurons in the M2 ϩ/ϩ hippocampus. This concept is supported by previous observations indicating that M 2 receptors are present on GABAcontaining nerve terminals throughout the hippocampus (Rouse et al, 1997;Hajos et al, 1998) and that activation of hippocampal muscarinic receptors inhibits GABA release from hippocampal interneurons (Ben Ari et al, 1981;Behrends and ten Bruggencate, 1993). Together, these findings are consistent with a model in which induction of STP and LTP requires the activity-dependent stimulation of presynaptic M 2 heteroceptors suppressing the GABA-mediated inhibition of CA1 pyramidal neurons.…”
Section: Discussionsupporting
confidence: 87%
“…؊/؊ mice Previous studies have shown that activation of hippocampal muscarinic receptors can disinhibit hippocampal pyramidal cells by reducing GABA release from interneurons (Ben Ari et al, 1981;Behrends and ten Bruggencate, 1993). We speculated that this effect might be mediated by M 2 receptors, offering a potential mechanism for the reduction in synaptic plasticity observed in the M2 Ϫ/Ϫ hippocampal slices.…”
Section: Bicuculline Restores Stp and Robust Ltp In Hippocampi From M2mentioning
confidence: 88%
“…Thus a modest dose of the GABAA receptor antagonist is effective in abolishing gamma frequency network synchrony, but still too low so as to precipitate the development of disinhibitory hypersynchrony. Moreover, these data also indicate that, in view of their presynaptic action on inhibitory terminals (Behrends & ten Bruggencate, 1993;Clarke et al 1997), neither carbachol nor kainate were sufficiently potent to trigger epileptic activity. We then tested whether rhythmic GABAA receptor-mediated inhibitory postsynaptic potentials (IPSPs) played a role in A, extracellular recordings of two neighbouring layer 4 sites showing the induction of oscillatory network activity due to the conjoint action of kainate and carbachol.…”
Section: Resultsmentioning
confidence: 88%
“…Reduction of principal cell adaptation in DG, CA3 and CA1 (Madison and Nicoll, 1984;Madison et al, 1987) 5. ACh suppresses inhibition of dentate granule cells (Bilkey and Goddard, 1985) and also decreases perisomatic inhibition of pyramidal cells, probably by suppressing release from basket cell terminals (Behrends and ten Bruggencate, 1993). Accordingly, in the model ACh suppresses inhibition in all model layers.…”
Section: Enhancement Of Ltp At Ca3 Recurrent Collateral Synapses Atmentioning
confidence: 85%